Eksistensi Eksistensi Kuli Panggul Perempuan di Pasar Pabean Surabaya Ditengah Maraknya Budaya Seksisme: Eksistensi kuli panggul perempuan - Asri, Julia Kumala (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2022)
This study focuses on knowing the existence of female porters at the Surabaya Customs Market amidst the rampant sexism culture. The theory used in this study is the theory of gender equality, where nowadays working women are often a hot topic of conversation. The method used in this research is observation and interview where the interview is conducted by interview guide and semi-structured method where the researcher can conduct interviews in a wide but within the corridor of related topics. The data analysis used in this study was carried out interactively from Miles and Huberman including, data reduction, data presentation, and drawing conclusions. In this study there were seven informants. Researchers found facts in the field that female porters often experience negative treatment from both the family environment and the surrounding environment. This treatment is degrading the work of female porters where this work is not commonly done by women. In this research, it is hoped that it will be able to make a major contribution to social studies material as teaching materials that are in accordance with KI and KD in schools, especially with regard to gender equality.